Analysis of transportation and logistics processes for soybeans in Brazil - Olivia Fliehr (Johann Heinrich von Thünen-Institut, 2013)
This study examines the relevance of Brazilian domestic transportation and logistics processes for agricultural bulk exports in terms of costs and CO2 emissions between farm gate and seaport, using the example of soybeans. To estimate the impact of logistics and transportation on the competitiveness of soybeans in a national comparison, export processes starting in four selected regions within the Sorriso-Santos corridor and travelling to the principal seaport for soybean exports in Santos-SP are evaluated. The analysis is based on agricultural statistics and data from field research as well as on information from expert interviews. Experts belong to the transportation and logistics sector, to the sector of agricultural production as well as to relating associations and research institutions. The results provide insight into the development and status quo of the domestic soybean market and infrastructure for transportation and storage of bulk materials. Structure and actors involved in the domestic supply chain are presented in a market analysis. A cost analysis elucidates a clear correlation of the export price (fob Santos) with the producer price (at the local spot market). The prices differ basically by the freight rates for domestic transportation. An impact assessment of CO2 emissions shows that rail transportation is in the specific cases not more efficient in terms of CO2 emissions than road transportation. This is due to a low utilization of the transport capacity on the train's return trips. The survey results also show the current bottlenecks and the potential and trends for the future development of the Brazilian logistics and transport sector for agricultural bulk products. The importance of efficient logistics and transportation processes for the competitiveness of soybeans on the international market is increasing with the relocation of the major soybean production areas into remote rural areas with underdeveloped infrastructure. The nationwide deficient network of transportation and storage infrastructure as well as of transshipment terminals leads to increased costs and capacity constraints. Monopoly-like structures and insufficient capacities in the regional rail system also exacerbate the problem of high freight rates. Recent public and private initiatives to improve the national infrastructure, particularly in the ports in northern Brazil, could lead to large improvements in the soybean logistics. – – In der vorliegenden Studie erfolgt eine Analyse der brasilianischen Logistik und des Inlandstransports für agrarische Schüttgüter am Beispiel von Sojabohnen. Um den Einfluss von Transport und Logistik auf die Wettbewerbsfähigkeit der Sojaproduktion in Brasilien zu ermitteln, wurde eine Markt- und Kostenanalyse für vier Anbaugebiete im Sorriso-Santos-Korridor mit abnehmenden Transportdistanzen zum Hauptexporthafen von Soja in Santos-SP durchgeführt. Hierfür wurden agrarstatistische Daten sowie Ergebnisse von Befragungen unter Experten aus dem Transportund Logistiksektor, aus der landwirtschaftlichen Produktion sowie aus Verbänden und der Wissenschaft ausgewertet. Die Ergebnisse geben dabei Aufschluss über Entwicklung und Status quo des Sojamarktes und der inländischen Infrastruktur für Transport und Lagerung von Schüttgütern. In einer Marktanalyse werden Struktur und beteiligte Akteure der inländischen Lieferkette dargestellt. Eine Kostenanalyse verdeutlicht, dass ein klarer Zusammenhang von Hafenpreis (fob Santos) und Produzentenpreis (am lokalen Spotmarkt) besteht. Die Preise unterscheiden sich im Wesentlichen nur durch die Frachtraten. Eine CO2-Bilanzierung verdeutlicht, dass der Schienentransport aufgrund geringer Auslastungen der Transportkapazitäten auf den Rückfahrten gegenüber dem Straßentransport nicht emissionseffizienter ist. Die Umfrageergebnisse zeigen darüber hinaus die aktuellen Engpässe sowie weitere Potenziale und Tendenzen zur künftigen Entwicklung des brasilianischen Logistik- und Transportsektors für Agrarerzeugnisse auf. Als zweitgrößter Exporteur auf dem Weltmarkt gehört Brasilien zu den Hauptversorgern der weltweiten Sojanachfrage. Der Einfluss von Logistik und Transport auf die Wettbewerbsfähigkeit von Sojabohnen auf dem internationalen Markt nimmt durch die Verlagerung der Hauptanbaugebiete in küstenferne und infrastrukturarme ländliche Räume zu. Die allgemein defizitäre Infrastruktur von Transportnetz, Lager und Verladeterminals führt zu erhöhten Kosten und Kapazitätsengpässen. Monopolähnliche Strukturen und unzureichende Kapazitäten im regionalen Eisenbahnbetrieb verschärfen zudem das Problem hoher Frachtpreise. Investitionen in den Ausbau der Infrastruktur, besonders in den Häfen im nördlichen Brasilien, mit privaten und öffentlichen Mitteln versprechen eine deutliche Optimierung der Logistik.
urn:nbn:de:gbv:253-201307-dn052162-2
Keywords: Q13; Q17; Q50; 330; Brazil; soybeans; infrastructure; logistics; transport; logistics costs; transportation costs; CO2-emissions; Brasilien; Soja; Infrastruktur; Logistik; Transport; Logistikkosten; Transportkosten; CO2-Emissionen